Surgical antibiotic prophylaxis: is the clinical practice based on evidence? - Pereira, Lucas Borges; Feliciano, Cinara Silva; Siqueira, Diego Silva [UNESP]; Bellissimo-Rodrigues, Fernando; Leira Pereira, Leonardo Regis (Inst Israelita Ensino & Pesquisa Albert Einstein, 2020)
Objective: To assess the surgical antibiotic prophylaxis. Methods: This was a descriptive study performed at a public tertiary care university hospital gathering prescription, sociodemographic and hospitalization data of inpatients admitted in 2014 who used antimicrobial drugs. This data were obtained from the hospital electronic database. The antimicrobial data were classified according to the anatomical, therapeutic chemical/defined daily dose per 1,000 inpatients. An exploratory analysis was performed using principal component analysis. Results: A total of 5,182 inpatients were prescribed surgical antibiotic prophylaxis. Of the total antimicrobial use, 11.7% were for surgical antibiotic prophylaxis. The orthopedic, thoracic and cardiovascular postoperative units, and postoperative intensive care unit comprised more than half of the total surgical antibiotic prophylaxis use (56.3%). The duration of antimicrobial use of these units were 2.2, 2.0, and 1.4 days, respectively. Third-generation cephalosporins and fluoroquinolones had the longest use among antimicrobial classes. Conclusion: Surgical antibiotic prophylaxis was inadequate in the orthopedic, postoperative intensive care, thoracic and cardiovascular postoperative, gynecology and obstetrics, and otolaryngology units. Therefore, the development and implementation of additional strategies to promote surgical antibiotic stewardship at hospitals are essential.
Keywords: Drug utilization review; Antibiotic prophylaxis; Drug resistance, microbial; Surgical wound infection/prevention & control; Infection control